HESCCO: development of good practice models for hES cell derivation. (January 2008) - Franklin, Sarah B; Hunt, Charles; Cornwell, Glenda; Peddie, Valerie; Desousa, Paul; Livie, Morag; Stephenson, Emma L; Braude, Peter R
One response of the UK research community to the public sensitivity and logistical complexity of embryo donation to stem cell research has been the formation of a national network of ''human embryonic stem cell coordinators'' (hESCCO). The aim of hESCCO is to contribute to the formation and implementation of national standards for hES cell derivation and banking, in particular the ethical protocols for patient information and informed consent. The hESCCO project is an innovative practical intervention within the broader attempt to establish greater transparency, consistency, efficiency and standardization of hES derivation in the UK. A major outcome of the hESCCO initiative has been the drafting and implementation of a national consent form. The lessons learned in this context may be relevant to other practitioners and regulators as a model of best practice in hES cell derivation.